Army of None : Autonomous Weapons and the Future of War - Scharre, Paul (New York W.W. Norton & Company, 2018)
"The era of autonomous weapons has arrived. Today around the globe, at least thirty nations have weapons that can search for and destroy enemy targets all on their own. Paul Scharre, a leading expert in next-generation warfare, describes these and other high tech weapons systems--from Israel's Harpy drone to the American submarine-hunting robot ship Sea Hunter--and examines the legal and ethical issues surrounding their use. 'A smart primer to what's to come in warfare' (Bruce Schneier), Army of None engages military history, global policy, and cutting-edge science to explore the implications of giving weapons the freedom to make life and death decisions. A former soldier himself, Scharre argues that we must embrace technology where it can make war more precise and humane, but when the choice is life or death, there is no replacement for the human heart."--Back cover
Include Illustrations and Index
Keywords: Military weapons--Technological innovations -- Robotics--Military applications -- Weapons systems--Technological innovations